Placenta mesenchymal stem cell-derived extracellular vesicles alleviate liver fibrosis by inactivating hepatic stellate cells through a miR-378c/SKP2 axis - Wenjie Zheng; Saiyan Bian; Shi Qiu; Colin E. Bishop; Meimei Wan; Nuo Xu; Xieyin Sun; Russel Clive Sequeira; Anthony Atala; Zhifeng Gu; Weixin Zhao (BMC, 2023)
Abstract Background Extracellular vesicles derived from mesenchymal stem/stromal cells (MSCs) have shown therapeutic effects on liver fibrosis. This study aimed to evaluate the effects of extracellular vesicles from placenta-derived MSCs (Pd-MSCs-EVs) on liver fibrosis at 3D/2D levels and explore the potential mechanisms. Methods The multicellular liver organoids, consisting of hepatocytes, hepatic stellate cells (HSCs), Kupffer cells, and liver sinusoidal endothelial cells, were observed for growth status, morphological changes, and metabolism. Human transformation growth factor- beta 1 (TGF-β1) was used to induce fibrosis at optimal concentration. The anti-fibrosis effects of Pd-MSCs-EVs were evaluated in liver organoids and HSCs models. Anti-fibrotic content of Pd-MSCs-EVs was identified by multiple experimental validations. Results TGF-β1 induced fibrosis in liver organoids, while Pd-MSCs-EVs significantly alleviated fibrotic phenotypes. Following serial verifications, miR-378c was identified as a potential key anti-fibrosis content. In contrast, miR-378c depletion decreased the anti-fibrotic effects of Pd-MSCs-EVs. Additionally, Pd-MSCs-EVs administration repressed TGF-β1-mediated HSCs activation at 2D or 3D levels. Mechanistically, exosomal miR-378c inactivated HSCs by inhibiting epithelial-mesenchymal transition (EMT) through stabilizing E-cadherin via targeting its E3 ubiquitin ligase S-Phase Kinase Associated Protein 2 (SKP2). Conclusion Pd-MSCs-EVs ameliorated TGF-β1-induced fibrosis by deactivating HSCs in a miR-378c/SKP2-dependent manner, which may be an efficient therapeutic candidate for liver fibrosis.